The Potential of Guava Leaf Extract as A Natural Preservation for Fish - Riyanto (International Journal of Ecophysiology, 2020)
Fish is kinds of food that easy to spoil. High protein content in fish makes the food is a good medium for microorganisms. People commonly buy fish for consumption, however, not all fish are consumed at the same time. Fishes were stored in freezer for several days or preserved with additional chemical preservation. The use of organic preservatives have no harm. This paper discussed guava (Psidium guajava L) leave as natural fish preservation. The objectives were to analyze the potency of the leaves as a natural preservation for mackerel fish (Rastrelliger sp.). Fime parameters used to determine the fish quality as follows : gills, eye, texture, odour and mucilage. The treatments were leaf methanolic extract with doses 0, 20, 40, 60 and 80%. Data were taken on from 1 to 5 days after storage. The results showed that (i) Fish quality was decline and start to depraved at 2 day storage, especially at control treatment (0% extract). Treatment at doses 60 and 80%, the fish quality were still relatively good over 3 days storage. Even though the fish samples have been starting spoilage, those fishes were still available to be consumed. At the same time, with the other treatment, the fish samples have been spoiled and no more available to be consumed. However, at 5th day of storage, all samples at all treatments were spoiled. Overall results, it can be concluded that extract of guava leaves can be has as fish preservativedosage